Ruh, Nafs, Aql, Qalb, dan Fitrah sebagai Potensi Dasar Manusia dalam Menjalankan Fungsi sebagai 'Abdullah: Tinjauan Filosofis dan Implikasinya dalam Pendidikan Islam - Muhammad Shidiq; Siti Rohimah (Lembaga Yasin AlSys, 2026)
Human beings in the Islamic perspective are creatures endowed with fundamental potentials originating from spiritual and physical dimensions. This study focuses on how ruh, nafs, ‘aql, qalb, and fitrah as basic human potentials can be understood philosophically and implied in Islamic education, particularly in the formation of a true ‘Abdullah. This study aims to analyze the nature of these five basic human potentials philosophically and integratively and to formulate their implications for curriculum development and Islamic educational practice. This study used a library research method with philosophical-analytical and descriptive-comparative approaches. Data were collected from primary sources in the form of the Qur’an, hadith, and the works of Muslim philosophers, as well as secondary sources in the form of reputable national and international journals published in the last decade. The data were analyzed using content analysis and critical-comparative techniques. The results showed that these five potentials are not separate entities but an integrative system that mutually supports one another: ruh as a divine substance, nafs as the totality of the self, ‘aql as a rational instrument, qalb as the center of spiritual consciousness, and fitrah as a primordial orientation toward monotheism. These potentials collectively underlie human ability to carry out the function of ‘Abdullah, or servant of Allah. The pedagogical implications of this study include the reconstruction of a curriculum based on spiritual potentials, the development of learning methods that integrate cognitive, affective, and spiritual dimensions, and the strengthening of the teacher’s role as a guide for students’ souls. The conclusion of this study affirms that authentic Islamic education needs to position the holistic development of ruh, nafs, ‘aql, qalb, and fitrah as the main foundation for realizing educational goals that culminate in total servitude to Allah Swt.